Targeting TUBB2B inhibits triple-negative breast cancer growth and brain-metastatic colonization - Qingling He; Jianyang Hu; Fung-Yin Ngo; Huiqi Zhang; Lin He; Hao Huang; Tan Wu; Yilin Pan; Zihan Yang; Yuanyuan Jiang; William C. Cho; Wah Cheuk; et al. (Journal of Experimental & Clinical Cancer Research, 2025)
Abstract Background The triple-negative subtype of breast cancer is particularly challenging to treat due to its aggressiveness with a high risk of brain metastasis, and the lack of effective targeted therapies. Tubulin beta 2B class IIb (TUBB2B), a β-tubulin isoform regulating axon guidance during embryonic development, was found to be overexpressed in various types of cancers including triple-negative breast cancer (TNBC). However, its functional roles in breast cancer or metastasis remain unclear. Methods To identify TUBB2B as a novel molecular target in TNBC, we performed bioinformatics analysis to assess the association of TUBB2B expression and survival of patients. RNAscope in situ hybridization was used to examine TUBB2B expression in clinical breast tumor samples. The effect of TUBB2B knockdown on TNBC growth and brain metastasis colonization was evaluated by in vitro and in vivo assays. Mass spectrometry (MS) and biochemical experiments were performed to explore the underlying mechanisms. Preclinical efficacy of targeting TUBB2B was determined in xenograft studies using the siRNA-gold nanoparticle (siRNA-AuNP) approach. Results TUBB2B, but not other β-tubulin isoforms, is frequently overexpressed in TNBC primary tumors as well as brain metastases. We also find that upregulation of TUBB2B is associated with poor prognosis in breast cancer patients. Silencing TUBB2B induces tumor cell death and inhibits the outgrowth of brain metastasis. Mechanistically, we identify eukaryotic translation elongation factor 1 alpha 1 (eEF1A1) as a novel interacting partner of TUBB2B, revealing a previously unexplored role of TUBB2B in translational regulation. In line with its neural-related functions, TUBB2B overexpression in TNBC cells activates astrocytes, which in turn upregulate TUBB2B in tumor cells. These findings suggest a feed-forward interaction between TUBB2B in TNBC cells and astrocytes that promotes brain metastatic colonization. Furthermore, we demonstrate the potent inhibition of TNBC xenograft growth as well as brain metastatic colonization using TUBB2B siRNA-AuNP treatment, indicating potential clinical applications of targeting TUBB2B for TNBC. Conclusions TUBB2B is a novel TNBC gene that plays a key role in promoting tumor cell survival and brain metastatic colonization, and can be targeted by siRNA-AuNPs as a treatment strategy.